ANTI-VIRUS AND BACTERIA MIST TESTING (KAVI-B) TO REMOVE ESCHERICHIA COLI AND STAPHYLOCOCCUS AUREUS BACTERIA - Tazi, Imam; Fitriasari, Prilya Dewi; Mulyono, Agus; Noor, Marvina Rizqi; Putri, Siska Emelda (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2021)
A disinfectant and antiseptic vaporizer has been made by using a vibrating membrane in the ultrasonic order. This method does not go through the stages of evaporation by heating the material. This machine is capable of converting ethanol in the liquid phase into the form of mist or vapor very quickly. Within 1 second when the engine is started, the cold ethanol material will turn into steam or mist. The concentration of the ethanol solution after and before evaporation did not change significantly. The change in ethanol concentration that occurs is only around 2-5%. The effect of decreasing colonies of Escerichia coli and Staphylococcus aureus bacteria after being given a mist containing 65% ethanol decreased exponentially. This spray has many advantages over using ethanol in liquid form. The sample size of the vaporized ethanol concentration greatly affects the evaporation produced by the KAVi-B engine. A very linear relationship was found between the concentration and the rate of evaporation. The linear relationship between the concentration of ethanol and the rate of evaporation has a linear regression value of Y = 0.2617X + 20.657 and R2 = 0.9908.